Humbug! : the politics of art criticism in New York City's penny press - Katz, Wendy Jean (New York : Empire State Editions, an imprint of Fordham University Press, 2020)
Mines the more than 300 newspapers published in New York City before the Civil War for art criticism, in order to trace the changing political positions of artists, artworks, and authors.
Cover -- Title Page -- Copyright -- Contents -- List of Illustrations -- Introduction: The Penny Press -- 1 The Aristocracy of Art and Bennett's Herald -- 2 Artists, Their Agents, and Press Manipulation -- 3 Old Masters versus Young America -- 4 The Penny Press's Utopian Alternative -- 5 The Genteel and the Bohemian -- 6 Rearing Statues amid Gothic Spires -- Conclusion: Art and Politics -- Acknowledgments -- Notes -- Index
Online resource; title from digital title page (viewed on April 13, 2020).
Includes bibliographical references and index.
In English.
JSTOR
Keywords: Art criticism -- New York (State) -- New York -- History -- 19th century; Penny newspapers -- New York (State) -- New York; Art -- Political aspects -- New York (State) -- New York -- History -- 19th century; Art and society -- New York (State) -- New York -- History -- 19th century; Critique d'art -- New York (État) -- New York -- Histoire -- 19e siècle.; Art -- Aspect politique -- New York (État) -- New York -- Histoire -- 19e siècle.; Art et société -- New York (État) -- New York -- Histoire -- 19e siècle.; HISTORY / United States / State & Local / Middle Atlantic (DC, DE, MD, NJ, NY, PA).; Art and society; Art criticism; Art -- Political aspects; Penny newspapers; New York (State) -- New York; 1800-1899; American Art; Antebellum; Art criticism; Civil War; Humbug; Newspapers; Penny press; Political parties; Politics; Working-class.; History